Demand Estimation with Expenditure Measurement Errors on the Left and Right Hand Side - Lewbel, Arthur (The Review of Economics and Statistics, 1996)
Let x be total consumption expenditures. Measurement errors in consumer budget allocation models cause unusual problems because errors in the dependent variables, consumption on individual goods, contribute to errors in the regressor x. Empirically adequate budget share models, like the AIDS, translog, and quadratic AIDS, are linear or quadratic in log x. It is shown that, for these specifications, two stage least squares fails to correct for the measurement error. A simple technique for recovering consistent estimates from two stage least squares is provided, along with an efficient generalized method of moments estimator. The method is applied to U.K. fuel demand data. Copyright 1996 by MIT Press.